Preparation method and application of oxide coated multifunctional resin
By depositing dual metal oxides on the surface of the resin, the function of the function of the resin material when processing complex VOCs and insufficient oxidation performance are solved, and the effect of high -efficiency adsorption and catalytic decomposition VOCS can be used, and the materials can be used circularly.
Patent Information
- Application Number
- CN202411296244.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-28
AI Technical Summary
Existing resin materials have single functions when dealing with complex VOCs, insufficient oxidation performance, active components are prone to wear and cannot be recycled, resulting in poor adsorption and oxidation performance.
The preparation method of oxide encapsion -type multi -functional resin is used to modify the resin through the coupling agent and use the oxidation and reduction of precipitation and water synthesis technology to deposit dual metal oxides on the surface of the resin to improve the catalytic decomposition efficiency of VOCs.
A large -capacity adsorption VOCS in gas phase is realized, and VOCs is catalyzed at low temperature to avoid secondary pollution. The material has high circulativity and stability.
Smart Images

Figure CN119368233A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a preparation method and application of an oxide-coated multifunctional resin, and belongs to the field of new material preparation and advanced oxidation technology. Background Art
[0002] With the continuous development of industry and technology, volatile organic compounds (VOCs) emitted from industrial processes such as machinery manufacturing, petrochemicals, pharmaceuticals, and spray coatings are one of the main factors causing ozone layer depletion, photochemical smog, and global warming. There are many types of VOCs, and VOCs containing heteroatoms such as Cl and S are one of the most difficult to deal with. In practical applications, the VOCs emission characteristics of most companies are very complex, containing both conventional VOCs and a large number of chlorine-containing VOCs (CVOCs for short), especially in the pharmaceutical, electronics, and fine chemical industries. Since the Cl element has a strong electronegativity, it is difficult to be biodegraded in a free state in nature, and it is easy to accumulate in organisms. It has a strong "three-cause effect", so it has become the focus of current air governance due to its environmental difficulty in degradation and persistence.
[0003] At present, the main VOCs treatment technologies include incineration, adsorption, condensation, biological, catalytic combustion, chemical spraying, etc. Due to the presence of chlorine, the use of combustion technology is prone to produce secondary highly toxic pollutants, such as dioxins, etc. Therefore, for complex VOCs components, adsorption has become the mainstream purification technology. The adsorption method mainly uses activated carbon, molecular sieves, macroporous adsorption resins, etc. as adsorbents. Among them, porous resins have attracted much attention due to their large specific surface area, strong hydrophobicity, and excellent adsorption performance.
[0004] The patent with publication number CN117000218A discloses a method for preparing a porous organic resin and is used to adsorb phenol in the liquid phase, which has super high phenol adsorption performance. However, adsorption is only to enrich the organic matter, and it is not disposed of, and secondary treatment is also required to increase the cost at the same time. Therefore, a suitable treatment method is needed after enrichment. In recent years, adsorption coupling advanced oxidation technology has received more attention. The principle of this technology is to first enrich VOC into an adsorbent, and then oxidize and degrade the adsorbed VOC by advanced oxidation technology, and its treatment efficiency mainly depends on the performance of the adsorption catalyst. Documents (Fuel, 2023,337,127130) report a method for loading ferrous ions on commercial porous resins by swelling impregnation, which improves the adsorption capacity of toluene, and then uses advanced oxidation technology to decompose the adsorbed toluene, and realizes the regeneration of resin adsorption capacity. However, the ferrous ions loaded on the resin by impregnation are easily dissolved in the liquid phase during the advanced oxidation process, so that the catalyst cannot be regenerated and cannot be recycled. The literature (Functional Materials, 2023, 54(05):5133-5140) reported a preparation method of a cationic resin-based iron-manganese-cerium adsorbent, which was first pretreated, soaked in dilute hydrochloric acid for 12 hours, dried and sieved, and then ferric chloride, ferrous sulfate, and cerium sulfate were weighed and dissolved and added to the resin carrier for oscillation and impregnation for 12 hours, rinsed after the reaction, and then potassium permanganate, sodium hydroxide, and sodium chloride solutions were added, and then oscillated for 12 hours, rinsed and dried to constant weight. This preparation method also uses the redox method, but the bonding between the oxide and the resin is not strong, the wear rate is high, the active components are easy to fall off, and the material life is short.
[0005] In summary, for the treatment of complex VOCs, there is an urgent need for new resin materials that can adsorb VOCs in large capacity in the gas phase, have strong firmness, catalytically decompose VOCs at low temperatures, do not produce secondary pollutants, and can be recycled. Summary of the invention
[0006] In order to solve the problem that resin materials have a single function and no oxidation performance, the active components of traditional preparation methods are easy to wear and cannot be recycled, resulting in poor adsorption and oxidation performance, the present application provides a preparation method and application of an oxide-coated multifunctional resin. The multifunctional resin uses resin as a carrier, which itself has super hydrophobicity and has a high adsorption capacity for complex VOCs. However, the resin has poor binding ability with inorganic oxides and is easy to wear and fall off. On this basis, the hydrophilic and lipophilic properties of the coupling agent are used to modify the resin to play a grafting role, so that the oxide can be firmly loaded on the resin surface. Subsequently, a redox precipitation method is used to precipitate highly uniformly dispersed bimetallic oxides on the resin surface to obtain oxide-coated resin seeds. Finally, hydrothermal synthesis is used to further regulate the loading amount of the bimetallic oxide, thereby improving the catalytic decomposition efficiency of VOCs.
[0007] This application adopts the following technical solutions:
[0008] According to one aspect of the present application, a method for preparing an oxide-coated multifunctional resin is provided, comprising the following steps:
[0009] S1, preparing an alcohol-water solution containing a coupling agent, placing a resin in the solution, and impregnating I to obtain a modified resin with a coupling agent grafted on the surface;
[0010] S2, placing the modified resin in step S1 into an aqueous solution of potassium permanganate, and immersing II to obtain a high-valent manganese modified resin suspension;
[0011] S3, adding an aqueous solution containing a low-valent metal salt and a divalent manganese salt to a suspension of a high-valent manganese-modified resin to form a precursor solution in which the high-valent manganese-modified resin is suspended, the metal precursor undergoes an oxidation-reduction reaction on the surface of the resin, and the reaction product solution is filtered and dried to obtain a resin seed with a bimetallic oxide shell layer precipitated on the surface;
[0012] The metal precursors are low-valent metal ions, divalent manganese ions and permanganate ions in the precursor liquid;
[0013] S4, placing the resin seeds of step S3 and a mixed aqueous solution containing potassium permanganate, a low-valent metal salt and a divalent manganese salt into a sealed container, and subjecting them to a hydrothermal reaction to finally obtain an oxide-coated multifunctional resin.
[0014] Optionally, in step S1, the volume ratio of the alcohol to water is 3:1 to 1:3, and the amount of the coupling agent used is 10% to 90% of the total volume of the alcohol-water solution containing the coupling agent.
[0015] Optionally, in step S1, the alcohol is selected from at least one of ethanol, methanol and isopropanol, preferably ethanol.
[0016] Optionally, in step S1, the immersion time I is 3 to 8 hours.
[0017] Optionally, in step S1, the silane coupling agent is selected from at least one of alkyl silane, vinyl silane, amino silane and epoxy silane.
[0018] Optionally, the alkylsilane is selected from at least one of hexadecyltrimethoxysilane and n-dodecyltriethoxysilane.
[0019] Optionally, the vinyl silane is selected from at least one of vinyl trimethoxy silane and vinyl triacetoxy silane.
[0020] Optionally, the aminosilane is selected from at least one of γ-aminopropyltriethoxysilane and γ-aminopropyltrimethoxysilane.
[0021] Optionally, the epoxy silane is selected from at least one of γ-glycidyloxypropyltrimethoxysilane and 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane.
[0022] Optionally, in step S1, the material of the resin is selected from at least one of polystyrene, polystyrene-divinylbenzene, and polyacrylic acid.
[0023] Optionally, in step S1, the silane coupling agent and the resin have the same lipophilic group;
[0024] The coupling agent and resin with the same lipophilic group are matched to achieve the best binding effect.
[0025] Optionally, step S1 further includes washing, filtering and drying after the impregnation I.
[0026] Optionally, in step S2, the weight ratio of potassium permanganate to water in the potassium permanganate aqueous solution is 1:100-500.
[0027] Optionally, in step S2, the time of immersion II is 0 to 60 minutes.
[0028] Optionally, in step S3, the metal element in the low-valent metal salt is selected from at least one variable-valent metal element of Fe, Co, Cu, and Ce.
[0029] In the present application, the anions in the low-valent metal salt and the divalent manganese salt are not strictly limited, and can form water-soluble salts, such as nitrates and sulfates.
[0030] Optionally, the ratio of the amount of resin in step S1 to the amount of potassium permanganate in step S2 is 1 g: (0.5-2) mmol.
[0031] Optionally, the ratio of the amount of resin used in step S1 to the amount of low-valent metal salt used in step S3 is 1 g: (0-2) mmol.
[0032] Optionally, the ratio of the amount of resin used in step S1 to the amount of divalent manganese salt used in step S3 is 1 g: (0-1.8) mmol.
[0033] In the above-mentioned usage ratio of the resin to the low-valent metal salt and the divalent manganese salt, the lower limit of the usage ratio of the low-valent metal salt and the divalent manganese salt does not include the endpoint value.
[0034] Optionally, the ratio of the amount of resin in step S1 to the amount of potassium permanganate in step S2 is any value among 1g:0.5mmol, 1g:0.75mmol, 1g:1mmol, 1g:1.25mmol, 1g:1.5mmol, 1g:1.75mmol, 1g:2mmol, or any range value therebetween.
[0035] Optionally, the ratio of the amount of resin in step S1 to the amount of low-valent metal salt in step S3 is any value among 1g:0.01mmol, 1g:0.05mmol, 1g:0.1mmol, 1g:0.5mmol, 1g:1mmol, 1g:1.5mmol, 1g:2mmol, or any range value therebetween.
[0036] Optionally, the ratio of the amount of resin in step S1 to the amount of divalent manganese salt in step S3 is any value among 1g:0.01mmol, 1g:0.05mmol, 1g:0.1mmol, 1g:0.5mmol, 1g:1mmol, 1g:1.5mmol, 1g:1.8mmol, or any range value therebetween.
[0037] Optionally, in step S3, the dropping speed is 1 to 10 ml / min.
[0038] In the present application, the concentrations of the low-valent metal salt and the divalent manganese salt in the aqueous solution containing the low-valent metal salt and the divalent manganese salt are not strictly limited, as long as the low-valent metal salt and the divalent manganese salt are completely dissolved in the aqueous solution. The higher the concentration, the more the loading.
[0039] Optionally, in step S3, the conditions for the redox reaction include: a reaction temperature of 10 to 90° C., stirring at a rate of 10 to 50 r / min during the reaction, and a stirring time of 40 to 120 min. The reaction starts from the first drop.
[0040] Optionally, step S3 further includes washing, filtering, drying and drying after the redox reaction.
[0041] Optionally, in step S3, the drying temperature is 60-100°C.
[0042] Optionally, in step S4, the conditions of the hydrothermal reaction include: a reaction temperature of 120 to 200° C. and a reaction time of 24 to 72 hours.
[0043] Optionally, in step S4, the amounts of potassium permanganate, low-valent metal salt and divalent manganese salt in the mixed aqueous solution are 1 to 5 times the amounts of potassium permanganate in the potassium permanganate aqueous solution in step S2 and the amounts of low-valent metal salt and divalent manganese salt in the mixed aqueous solution in step S3, respectively.
[0044] Optionally, step S4 further includes washing and filtering the product after the hydrothermal reaction is completed, and then drying it at 60-100° C. for 5-20 hours.
[0045] In step S4, the metal element in the low-valent metal salt is selected from at least one variable-valent metal element of Fe, Co, Cu, and Ce;
[0046] Optionally, in step S4, the amount of the low-valent metal salt and the divalent manganese salt used is 1:0.5-9 in terms of the molar ratio of the variable-valent metal element to the manganese element.
[0047] According to another aspect of the present application, there is provided a use of an oxide-coated multifunctional resin prepared by the above method as a catalyst in purifying organic waste gas containing dichloromethane.
[0048] Optionally, the following steps are included:
[0049] Adsorption process: passing the organic waste gas containing dichloromethane into an adsorption device loaded with the oxide-coated multifunctional resin, so that the organic waste gas containing dichloromethane is in contact with the oxide-coated multifunctional resin;
[0050] Purification process: When the adsorption process reaches a saturated adsorption state, the hydrogen peroxide or persulfate solution is circulated into the adsorption equipment to circulate and rinse the oxide-coated multifunctional resin, and the material is regenerated in situ and circulated for the adsorption process.
[0051] The method for purifying dichloromethane organic waste gas by using the oxide-coated multifunctional resin prepared by the method of the present application as a catalyst for adsorption / oxidation comprises the following steps:
[0052] (1) First, the resin is assembled into an adsorption device, and the waste gas mixed with dichloromethane passes through the above device and is adsorbed into the resin pores after contacting the resin.
[0053] (2) After the dichloromethane adsorption reaches saturation, the prepared hydrogen peroxide solution is introduced, and the enriched high-concentration gaseous dichloromethane undergoes a multiphase Fenton-like reaction inside and on the surface of the resin. The liquid phase is continuously circulated through the adsorption layer by a peristaltic pump, causing the dichloromethane to be oxidized and degraded into carbon dioxide, water, and chloride ions.
[0054] (3) After the multiphase Fenton-like reaction, the resin is purged with air at room temperature, and after cooling to room temperature, it can adsorb dichloromethane again, thereby achieving adsorption / oxidation cycle purification of dichloromethane.
[0055] The beneficial effects of this application include:
[0056] (1) The oxide-coated multifunctional resin provided in the present application uses resin as a carrier, and the resin is modified by a coupling agent. The coupling agent's amphiphilic and hydrophilic properties are used as a "bridge" to connect the resin and the bimetallic oxide, thereby improving the binding ability of organic and inorganic substances, enhancing the firmness of the active components, and increasing the service life and stability of the material.
[0057] (2) Developed a combined preparation method of “redox precipitation-hydrothermal synthesis” to effectively load bimetallic oxides onto the resin surface and prepare a new type of structurally controllable oxide-coated resin core-shell structure material. On the basis of the original adsorption properties of the resin, the material is endowed with catalytic oxidation properties, thereby obtaining a new dual-functional material with adsorption and advanced oxidation properties.
[0058] (3) For complex chlorine-containing VOCs components, the new material has a high hydrophobicity, which is conducive to its effective adsorption of VOCs in complex high-humidity atmospheres; after adsorption saturation, the bimetallic oxide of the shell has catalytic oxidation properties as a Fenton-like catalyst. Under the oxidation of hydrogen peroxide or persulfate, VOCs can be decomposed into harmless CO2 and water at room temperature without producing secondary toxic byproducts such as nitrogen oxides and dioxins; at the same time, the new material can be regenerated in situ and can be recycled, reducing the cost of VOCs treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 Physical pictures of the PDVB resin (a) and the prepared coated PDVB@FeMn sample (b) in Example 1.
[0060] Figure 2 Schematic diagram of the testing device for VOCs adsorption performance of examples and comparative examples.
[0061] Figure 3 Schematic diagram of the testing device for the advanced oxidation performance of VOCs of the examples and comparative examples.
[0062] Figure 4 Schematic diagram of the VOCs adsorption-in-situ advanced oxidation cycle test device for the sample in Example 1. DETAILED DESCRIPTION
[0063] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0064] Three resins with different structures, polystyrene (PVB), polystyrene-divinylbenzene (PDVB), and polyacrylic acid (PAA), were purchased from Xi'an Lanxiao Technology New Materials Co., Ltd. in the shape of microspheres with a diameter of about 1 mm. Different types of silane coupling agents were purchased from Hubei Xinlantian New Materials Co., Ltd. with a purity of >99%. Activated carbon was purchased from Ningxia Jinpeng Carbon Co., Ltd., model JPZ5.0. HZSM-5 molecular sieve was purchased from Tianjin Nanhua Catalyst Co., Ltd. with a Si / Al ratio of 40.
[0065] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0066] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.
[0067] According to one embodiment of the present application, a method for preparing an oxide-coated multifunctional resin comprises the following steps: firstly preparing a coupling agent alcohol-water solution to swell the resin, then mixing the resin with a potassium permanganate solution, and then dripping a solution containing a low-valent metal and Mn 2+ The mixed solution is precipitated on the resin surface through redox reaction to form an oxide shell layer, and finally the oxide loading amount is further regulated by hydrothermal synthesis. After filtration and drying, the oxide-coated multifunctional resin is obtained.
[0068] According to one embodiment of the present application, a method for preparing an oxide-coated multifunctional resin comprises the following steps:
[0069] Step 1: prepare a certain mass ratio of alcohol-water-silane coupling agent solution, weigh a certain amount of resin balls and immerse them in the solution for a period of time, then wash and dry them;
[0070] Step 2: Weigh low-valent metal salts, divalent manganese salts and potassium permanganate according to a certain loading amount and a certain molar ratio of variable-valent metal and manganese element, mix the weighed potassium permanganate with deionized water in a certain mass ratio, add resin beads and stir for a period of time, and separately mix the weighed low-valent metal salts and divalent manganese salts, and add deionized water until they are completely dissolved;
[0071] Step 3: adding the mixed solution of low-valent metal and divalent manganese to the suspension of small balls soaked in potassium permanganate at a certain temperature and at a certain rate, stirring at a certain stirring rate for a period of time;
[0072] The following reaction occurs:
[0073] MnO4 - +3e - +2H2O→MnO2↓+4HO -
[0074] Mn 2+ +2H2O→MnO2↓+2e - +4H +
[0075] 2M x+ +yH2O→M2Oy↓+2(yx)e - +2yH +
[0076] The reaction uses low-valent metal, divalent manganese and permanganate as precursors, so that a redox reaction occurs between the three. During the reaction, a redox reaction occurs through the rapid transfer of electrons between the low-valent metal salt and / or divalent manganese precursor and the heptavalent manganese precursor, and a bimetallic oxide precipitate is simultaneously generated on the resin surface, thereby obtaining a resin seed uniformly loaded with the bimetallic oxide.
[0077] Step 4: Filter the obtained resin seeds, wash and dry them, put them into a hydrothermal kettle and add a certain amount of potassium permanganate, low-valent metal salt and divalent manganese salt solution. The proportion of metal precursors is consistent with that in step 2. Perform hydrothermal reaction at a certain temperature for a period of time. Finally, wash and dry them to obtain an oxide-coated multifunctional resin.
[0078] Example 1
[0079] At room temperature, a mixed solution of ethanol (25 ml)-water (25 ml)-vinyltrimethoxysilane (50 ml) was prepared, wherein the volume ratio of the coupling agent was 50%. 1 g of PDVB was taken, swollen for 5 hours, and then washed and dried to obtain modified PDVB. Ferrous sulfate was selected as the variable valence metal salt. 0.038g potassium permanganate, 0.030g manganese nitrate solution (mass ratio of 50%) and 0.113g ferrous sulfate heptahydrate were weighed according to the iron-manganese ratio of 1:1. The weighed potassium permanganate was dissolved in 38ml deionized water, and the modified PDVB was added and stirred for 20min. The weighed ferrous salt and manganese nitrate solution were mixed, deionized water was added until completely dissolved, and the mixture was added dropwise to the potassium permanganate solution at a rate of 4ml / min in a water bath at 80°C. After magnetic stirring at a speed of 30r / min for 60min, the mixture was filtered and dried to obtain resin seeds uniformly loaded with bimetallic oxides. The resin seeds were placed in a hydrothermal kettle and potassium permanganate, manganese nitrate solution and ferrous sulfate heptahydrate with a mass three times that of the previous ones were added. Water was added until completely dissolved, and the mixture was hydrothermally heated at 160°C for 48h. After being taken out and washed, the mixture was placed in an oven and dried at 80°C for 12h to obtain an oxide-coated multifunctional resin. The actual pictures of the obtained samples and PDVB resin are attached. Figure 1 shown.
[0080] Example 2
[0081] The preparation method is the same as that of Example 1, except that a mixed solution of ethanol (45 ml)-water (45 ml)-vinyltrimethoxysilane (10 ml) is prepared, wherein the volume ratio of the coupling agent is 10%.
[0082] Example 3
[0083] The preparation method is the same as that of Example 1, except that: a mixed solution of ethanol (5 ml)-water (5 ml)-vinyltrimethoxysilane (90 ml) is prepared, wherein the volume ratio of the coupling agent is 90%.
[0084] Comparative Example 1
[0085] The preparation method is the same as that of Example 1, except that: a mixed solution of ethanol (50 ml) and water (50 ml) is prepared, wherein the volume ratio of the coupling agent is 0%.
[0086] Test Example 1
[0087] The wear rate of the oxide-coated multifunctional resins prepared in the above Examples 1 to 3 and Comparative Example 1 was measured.
[0088] The evaluation method is as follows:
[0089] The wear rate of the catalyst is generally measured by the rotating collision method and the high-speed air injection method. According to the wear of the catalyst during actual use, fixed-bed catalysts generally use the former method, while fluidized-bed catalysts mostly use the latter method. The VOCs adsorption process belongs to a fixed-bed reaction, so we use the rotating collision method for determination. The material to be tested is placed in a rotating container, and it rolls up and down during the rotation of the container and is worn; after a period of time, the sample is taken out and the fine powder is sieved out. The intensity data is expressed as the amount of fine powder produced per unit mass of the sample, that is, the wear rate.
[0090] Table 1 Effect of coupling agent dosage on material wear rate
[0091] Example 1 Example 2 Example 3 Comparative Example 1 Wear rate 0.03% 0.53% 0.09% 3.54%
[0092] From the above data, it can be seen that the wear rate of the sample in Example 1 is the lowest, while the wear rate of the sample without using coupling agent in Comparative Example 1 is the highest, indicating that the coupling agent in the present invention has a significant reinforcing effect on the active component, but too low a coupling agent dosage has no obvious effect (Example 2), and too high a coupling agent dosage will cause it to be unable to be completely dissolved and emulsification will occur (Example 3), so the coupling agent dosage in Example 1 is the optimal dosage.
[0093] Comparative Example 2
[0094] The preparation method is the same as that of Example 1, except that the resin type is PVB.
[0095] Comparative Example 3
[0096] The preparation method is the same as that in Example 1, except that the resin type is PAA.
[0097] Comparative Example 4
[0098] The preparation method is the same as that of Example 1, except that the coupling agent is hexadecyltrimethoxysilane.
[0099] Comparative Example 5
[0100] The preparation method is the same as that of Example 1, except that the coupling agent is γ-aminopropyltriethoxysilane.
[0101] Test Example 2
[0102] The wear rate of the oxide-coated multifunctional resins prepared in the above Example 1 and Comparative Examples 2 to 5 was measured. The evaluation method was the same as that of Test Example 1.
[0103] Table 2 Effect of coupling agent type and resin type on material wear rate
[0104] Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Wear rate 0.03% 0.05% 0.13% 0.20% 0.18%
[0105] From the above data, it can be seen that the wear rates of the samples in Example 1 and Comparative Example 2 are relatively low, indicating that the vinyl coupling agent has good compatibility with the vinyl resins PVB and PDVB, while the lipophilic groups of the coupling agents in Comparative Examples 3 to 5 are different from the resin groups, and the compatibility is significantly reduced, indicating that the coupling agent with the same lipophilic group is matched with the resin and has the best bonding effect.
[0106] Example 4
[0107] The preparation method is the same as that in Example 1, except that the variable-valence metal is Cu, the variable-valence metal salt is cuprous nitrate trihydrate, 0.057 g of potassium permanganate solid, 0.044 g of manganese nitrate solution, and 0.145 g of cuprous nitrate trihydrate are weighed, and potassium permanganate is dissolved in 57 ml of deionized water.
[0108] Example 5
[0109] The preparation method is the same as that in Example 1, except that the variable-valence metal is Co, the variable-valence metal salt is cobalt nitrate hexahydrate, 0.037 g of potassium permanganate solid, 0.030 g of manganese nitrate solution, and 0.115 g of cobalt nitrate hexahydrate are weighed, and potassium permanganate is dissolved in 37 ml of deionized water.
[0110] Example 6
[0111] The preparation method is the same as that in Example 1, except that the variable-valence metal is Ce, the variable-valence metal salt is cerium nitrate hexahydrate, 0.037 g of potassium permanganate solid, 0.014 g of manganese nitrate solution, and 0.168 g of cuprous nitrate trihydrate are weighed, and potassium permanganate is dissolved in 37 ml of deionized water.
[0112] Test Example 3
[0113] The VOCs adsorption performance and catalytic performance of the oxide-coated multifunctional resins prepared in the above Examples 1 and 4 to 6 were evaluated.
[0114] The evaluation method is as follows:
[0115] Determination of VOCs adsorption: Take 1g of the sample to be tested and place it in the Figure 2 The fixed bed adsorption experiment was carried out in the sample tube shown. The adsorption temperature was set at 30°C, the initial concentration of dichloromethane was controlled at 600ppm, the moisture content of the atmosphere was 4vol%, and the space velocity was 8500h ~1 The total gas flow rate was 200 ml / min. The tail gas was connected to a gas chromatograph (FuLi GC-9790II) to detect the concentration of dichloromethane before and after adsorption. The adsorption curve was obtained. The dynamic adsorption capacity of the sample was calculated according to the breakthrough point when the dichloromethane concentration reached 10% of the initial concentration.
[0116] Determination of VOCs advanced oxidation activity: Take 1g of the sample to be tested and place it in the Figure 3 In the continuous advanced oxidation reaction device shown in the figure, the temperature of the catalytic device is set at 30°C, the initial concentration of dichloromethane is controlled at 100ppm, the total gas flow rate is 50ml / min, potassium persulfate is selected as the oxidant, the concentration is set to 3g / L, pH=7, the tail gas is connected to a gas chromatograph (FuLi GC-9790II), the changes in the types of products before and after catalytic oxidation, and the changes in the concentration of the reactant dichloromethane are detected, and the decomposition efficiency of dichloromethane that changes with time is calculated, as shown in Table 4.
[0117] Table 3 Effect of bimetallic species on dichloromethane adsorption
[0118] Example 1 Example 4 Example 5 Example 6 Bimetallic Type Fe-Mn Cu-Mn Co-Mn Ce-Mn Dynamic adsorption capacity 241mg / g 209mg / g 226mg / g 198mg / g
[0119] Table 4 Effect of bimetallic species on catalytic decomposition efficiency of dichloromethane
[0120] Reaction time Example 1 Example 4 Example 5 Example 6 Bimetallic Type Fe-Mn Cu-Mn Co-Mn Ce-Mn 1min 99.9% 99.9% 99.9% 99.9% 30min 99.9% 80.8% 85.2% 78.8% 60min 93.3% 72.7% 77.7% 66.4% 120min 74.3% 51.5% 62.3% 49.4%
[0121] From the above data, it can be seen that only dichloromethane was detected before and after the reaction, and no byproducts such as nitrogen oxides, polychloromethane, and dioxins were detected, indicating that the catalytic decomposition efficiency of the room temperature advanced oxidation process is high, and dichloromethane can be deeply degraded to avoid the formation of toxic byproducts. Comparing different samples, the Fe-Mn bimetallic in Example 1 has the highest adsorption capacity for dichloromethane and the best catalytic performance, indicating that the variable valence metal Fe in the present invention is the optimal value.
[0122] In order to further investigate the effect of Fe / Mn ratio on dichloromethane adsorption capacity and advanced oxidation performance, samples with different Fe / Mn ratios were prepared. The preparation method is as follows:
[0123] Example 7
[0124] The preparation method is the same as that in Example 1, except that the Fe / Mn ratio is 2:1, 0.031 g of potassium permanganate solid, 0.009 g of manganese nitrate solution, and 0.137 g of ferrous sulfate heptahydrate are weighed, and potassium permanganate is dissolved in 31 ml of deionized water.
[0125] Example 8
[0126] The preparation method is the same as that in Example 1, except that the Fe / Mn ratio is 1:6, 0.060 g of potassium permanganate solid, 0.093 g of manganese nitrate solution, and 0.041 g of ferrous sulfate heptahydrate are weighed, and potassium permanganate is dissolved in 60 ml of deionized water.
[0127] Test Example 4
[0128] The VOCs adsorption performance and catalytic performance of the oxide-coated multifunctional resins prepared in the above Examples 1 and 7-8 were evaluated. The evaluation method was the same as that in Test Example 3.
[0129] Table 5 Effect of different Fe / Mn on dichloromethane adsorption and oxidation performance
[0130] Example 1 Example 7 Example 8 Dynamic adsorption capacity 241mg / g 234mg / g 229mg / g 60min degradation rate 93.3% 78.6% 82.6%
[0131] According to the above data, the adsorption amount and degradation rate of dichloromethane in Example 1 are both the highest, indicating that the Fe / Mn ratio of 1:1 is the optimal value in the present invention.
[0132] In order to further investigate the effect of Fe-Mn loading on dichloromethane adsorption capacity and advanced oxidation performance, samples with different Fe-Mn loading were prepared. The preparation method is as follows:
[0133] Example 9
[0134] The preparation method is the same as that of Example 1, except that the resin seeds are placed in a hydrothermal kettle and potassium permanganate, manganese nitrate solution and ferrous sulfate heptahydrate in an amount twice the mass of the previous amount are added.
[0135] Example 10
[0136] The preparation method is the same as that of Example 1, except that the resin seeds are placed in a hydrothermal kettle and 5 times the mass of potassium permanganate, manganese nitrate solution and ferrous sulfate heptahydrate are added.
[0137] Test Example 5
[0138] The VOCs adsorption performance and catalytic performance of the oxide-coated multifunctional resins prepared in Examples 1 and 9 to 10 were evaluated using the same evaluation method as in Test Example 3.
[0139] Table 6 Effect of different Fe-Mn loadings on dichloromethane adsorption and oxidation performance
[0140] Example 1 Example 9 Example 10 Fe-Mn loading 6.6wt% 2.1wt% 10.3wt% Dynamic adsorption capacity 241mg / g 258mg / g 189mg / g 60min degradation rate 93.3% 58.6% 95.6%
[0141] According to the above data, Example 9 has the highest adsorption capacity for dichloromethane, which is due to its low Fe-Mn loading, which has little effect on the pore structure of the resin carrier, but the fewer active components lead to its worst catalytic oxidation ability; Example 10 has the highest degradation rate for dichloromethane, but due to the large loading, the Fe-Mn oxide in the outer layer has a blocking effect on the pore structure of the resin, resulting in a significant decrease in the adsorption capacity of dichloromethane. Taking the above factors into consideration, the Fe-Mn loading in Example 1 is the optimal value.
[0142] In order to further investigate the adsorption capacity of dichloromethane for the samples under high humidity environment, samples with different carriers were prepared. The preparation method is as follows:
[0143] Comparative Example 6
[0144] The preparation method is the same as that in Example 1, except that the carrier is activated carbon.
[0145] Comparative Example 7
[0146] The preparation method is the same as that in Example 1, except that the carrier is HZSM-5 molecular sieve.
[0147] Test Example 6
[0148] The VOCs adsorption performance of the oxide-coated multifunctional materials prepared in Example 1 and Comparative Examples 6 to 7 was evaluated. The evaluation method was the same as that in Test Example 3.
[0149] Table 7 Effect of exhaust gas moisture content on dichloromethane adsorption of different carrier samples
[0150] Exhaust gas moisture content Example 1 Comparative Example 6 Comparative Example 7 0vol% 227mg / g 326mg / g 195mg / g 4vol% 241mg / g 91mg / g 158mg / g 7vol% 239mg / g 43mg / g 128mg / g 12vol% 238mg / g 7mg / g 87mg / g
[0151] According to the above data, the resin carrier of Example 1 still has a high adsorption capacity of dichloromethane in a high humidity environment, and the dynamic adsorption capacity is even higher than that in a dry gas atmosphere. The activated carbon in Comparative Example 6 has the largest adsorption capacity in a dry atmosphere, but the adsorption capacity decreases rapidly in a water-containing atmosphere, and almost loses its dichloromethane adsorption capacity at high humidity. The adsorption capacity of the molecular sieve carrier in Comparative Example 7 also decreases significantly with increasing humidity. This is because the molecular sieve carrier itself has poor water resistance, which shows that the resin carrier in Example 1 is suitable for complex exhaust gas conditions with high humidity.
[0152] Test Example 7
[0153] In order to investigate the in-situ regeneration and recycling performance of the sample, an adsorption / in-situ oxidation cyclic purification test was carried out on Example 1.
[0154] The evaluation method is as follows:
[0155] The adsorption method of dichloromethane is consistent with the method for determining the amount of VOCs adsorption in Test Example 3. The regeneration method is as shown in the attached Figure 4 As shown, after adsorption saturation, the gas pipeline is closed, the liquid pipeline is opened, and the sample is circulated and cleaned with a 3g / L potassium persulfate solution for 1h. The sample is then taken out, and the dichloromethane residue on the sample surface, the gaseous residue in the potassium persulfate solution bottle and the liquid residue are detected according to the ecological environment standard (HJ 620-2011). The total amount of dichloromethane residue is recorded as the total dichloromethane residue, and the dichloromethane removal efficiency can be calculated. The sample is then reinstalled into the adsorption device, switched to the gas pipeline to repeat the adsorption-in-situ oxidation experiment, and the test is cycled 5 times in sequence.
[0156] Table 8 Dichloromethane adsorption and removal efficiency in the cycle test of Example 1
[0157] Cycle times 1 2 3 4 5 Adsorption capacity 241mg / g 240mg / g 238mg / g 238mg / g 237mg / g Liquid phase residue 0.022mg / g 0.054mg / g 0.087mg / g 0.127mg / g 0.153mg / g Gas phase residue <0.001mg / g <0.001mg / g <0.001mg / g <0.001mg / g <0.001mg / g Solid phase residue <0.001mg / g <0.001mg / g <0.001mg / g <0.001mg / g <0.001mg / g Removal efficiency >99.9% >99.9% >99.9% >99.9% >99.9%
[0158] From the test results, it can be seen that the adsorption capacity only decreased slightly during the 5 cycles. At the same time, only trace amounts of residual dichloromethane were detected in the liquid phase, and no residues were detected in the gas phase and solid phase, indicating that the sample has a high regeneration efficiency and good cycle stability.
[0159] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing an oxide-coated multifunctional resin, characterized in that: The steps include: S1, preparing an alcohol-water solution containing a coupling agent, placing a resin in the solution, and impregnating I to obtain a modified resin with a coupling agent grafted on the surface; S2, placing the modified resin in step S1 into an aqueous solution of potassium permanganate, and immersing II to obtain a high-valent manganese modified resin suspension; S3, adding an aqueous solution containing a low-valent metal salt and a divalent manganese salt to a suspension of a high-valent manganese-modified resin to form a precursor solution in which the high-valent manganese-modified resin is suspended, the metal precursor undergoes an oxidation-reduction reaction on the surface of the resin, and the reaction product solution is filtered and dried to obtain a resin seed with a bimetallic oxide shell layer precipitated on the surface; The metal precursors are low-valent metal ions, divalent manganese ions and permanganate ions in the precursor liquid; S4, placing the resin seeds of step S3 and a mixed aqueous solution containing potassium permanganate, a low-valent metal salt and a divalent manganese salt into a sealed container, and subjecting them to a hydrothermal reaction to finally obtain an oxide-coated multifunctional resin.
2. The preparation method according to claim 1, characterized in that: In step S1, the volume ratio of the alcohol to water is 3:1 to 1:3, and the amount of the coupling agent is 10% to 90% of the total volume of the alcohol-water solution containing the coupling agent; Preferably, in step S1, the time of the immersion I is 3 to 8 hours.
3. The preparation method according to claim 1, characterized in that: In step S1, the silane coupling agent is selected from at least one of alkyl silane, vinyl silane, amino silane and epoxy silane; Preferably, in step S1, the material of the resin is selected from at least one of polystyrene, polystyrene-divinylbenzene, and polyacrylic acid.
4. The preparation method according to claim 1, characterized in that: In step S2, the weight ratio of potassium permanganate to water in the potassium permanganate aqueous solution is 1:100-500.
5. The preparation method according to claim 1, characterized in that: In step S2, the time of immersion II is 0 to 60 minutes.
6. The preparation method according to claim 1, characterized in that: In step S3, the metal element in the low-valent metal salt is selected from at least one variable-valent metal element of Fe, Co, Cu, and Ce; Preferably, the ratio of the amount of resin in step S1 to the amount of potassium permanganate in step S2 is 1 g: (0.5-2) mmol; Preferably, the ratio of the amount of resin used in step S1 to the amount of low-valent metal salt used in step S3 is 1 g: (0-2) mmol; Preferably, the ratio of the amount of the resin in step S1 to the amount of the divalent manganese salt in step S3 is 1 g: (0-1.8) mmol.
7. The preparation method according to claim 1, characterized in that: In step S3, the dropping speed is 1 to 10 ml / min; Preferably, in step S3, the conditions for the redox reaction include: a reaction temperature of 10 to 90° C., a stirring rate of 10 to 50 r / min during the reaction, and a stirring time of 40 to 120 min; Preferably, in step S3, the drying temperature is 60-100°C.
8. The preparation method according to claim 1, characterized in that: In step S4, the conditions of the hydrothermal reaction include: reaction temperature of 120 to 200° C., reaction time of 24 to 72 h; Preferably, in step S4, the amounts of potassium permanganate, low-valent metal salt and divalent manganese salt in the mixed aqueous solution are 1 to 5 times the amounts of potassium permanganate in the potassium permanganate aqueous solution in step S2 and the amounts of low-valent metal salt and divalent manganese salt in the mixed aqueous solution in step S3, respectively. Preferably, step S4 further comprises washing and filtering the product after the hydrothermal reaction is completed, and then drying it at 60-100° C. for 5-20 hours.
9. Use of the oxide-coated multifunctional resin prepared according to the method according to any one of claims 1 to 8 as a catalyst in purifying organic waste gas containing dichloromethane.
10. The use according to claim 9, characterized in that: The steps include: Adsorption process: passing the organic waste gas containing dichloromethane into an adsorption device loaded with the oxide-coated multifunctional resin, so that the organic waste gas containing dichloromethane is in contact with the oxide-coated multifunctional resin; Purification process: When the adsorption process reaches the saturated adsorption state, the hydrogen peroxide or persulfate solution is circulated into the adsorption equipment to circulate and rinse the oxide-coated multifunctional resin, so that the dichloromethane is oxidized and degraded, and the material is regenerated in situ and used in the adsorption process to achieve recycling.
Citation Information
Patent Citations
Preparation method of resin with porous structure and high phenol adsorption performance
CN117000218A
Cited By
Enhanced activated carbon for organic waste gas and preparation method thereof
CN121103335A
Enhanced activated carbon for organic waste gas and method for preparing the same
CN121103335B